Upaya Relaksasi Progresif Untuk Mengurangi Nyeri Dan Cemas Pada Ny.L Dengan Gastritis - Nurul Atifah, Ifka, Supratman, Ph.D (2017)
Gastitis is inflammation or swelling of the mucosa of the stomach. One cause of gastritis is the stress that camefrrom anxiety, and gastritis causes pain to the suffurer, pain is an unpleasant feeling for some people and often associated with damage to the body which is a warning against the threats that are actual or potential. Gastritis disease hazard if allowed to continue would damage the function of the stomach and can increase the risk for gastric cancer to cause death. The percentage of incidence of gastritis in Indonesia is 40,8% according to the WHO, the incidence of gastritis in some areas in Indonesia is quite high prevalence of 238.452 cases from 274.386.952 inhabitants. To reduce anxiety and pain can be done progressive relaxation technique. In writing this report the authors use the method of case study was conducted at the Ngreco using the nursing process. In collecting the data using instruments such as interviews, physical examinations and observation. Then, analyze data, formulate a diagnosis, intervention, implementation and evaluation. These results are after four visits to their home and clients progressive relaxation techniques nonpharmacological pain was reduced and anxious is reduced, goal in particular was can to know about the health problems of gastritis, so the family is also can treat to prevent recurrence, the problem is resolved, but still advice Ny.L to keep diet, avoiding taboos and perfom progressive relaxation if the pain and anxiety arise.